Therapeutic Potential of Quercetin in Type 2 Diabetes Based on a Network Pharmacology Study - Basaldúa-Maciel, Viridiana; Guzmán-Flores, Juan Manuel; Reyes-Chaparro, Andrés; Martínez-Esquivias, Fernando (Current Topics in Medicinal Chemistry, 2025)
IntroductionCurrently, there are pharmacological treatments for type 2 diabetes (T2D), but these are ineffective. Quercetin is a flavonoid with antidiabetic properties.ObjectiveThis research aimed to identify the molecular mechanism of Quercetin in T2D from network pharmacology.MethodsWe obtained T2D-related genes from MalaCards and DisGeNET, while potential targets for Quercetin were sourced from SwissTargetPrediction and Comparative Toxicogenomics databases. The overlapping genes were identified and analyzed using ShinyGO 0.77. Subsequently, we constructed a protein-protein interaction network using Cytoscape, conducted molecular docking analyses with SwissDock, and validated the results through molecular dynamics simulation in GROMACS.ResultsQuercetin is involved in apoptotic processes and in the regulation of insulin activity, estrogen, prolactin and EGFR receptor. The key driver genes AKT1, GSK3B, SRC, IGF1R, MMP9, ESR2, PIK3R1, and MMP2 showed high concordance in the molecular docking study, and molecular dynamics showed stability between Quercetin and ESR2 and PIK3R1.ConclusionsOur work helps to identify the molecular mechanism and antidiabetic effect of quercetin, which needs to be studied experimentally.
Keywords: T2D